THE EFFECT OF COMMUNICATION AND WORK DISCIPLINE ON PERFORMANCE OF EMPLOYEES OF THE REGIONAL DEVELOPMENT PLANNING AGENCY (BAPPEDA) OF WAY KANAN DISTRICT - Dharmawan .; Yosi Yulia (Saburai International Journal of Social Sciences and Development, 2021)
The purpose of this study is to determine the effect of communication on employee performance and the effect of work discipline on employees and want to know the effect of communication and work discipline together on the performance of the Regional Development Planning Agency of Way Kanan Regency. The data collection technique was carried out by distributing questionnaires/questionnaires to 35 respondents using the SPSS program. The study results show the following: that Communication (X1) affects the performance of employees of the Regional Development Planning Agency of Way Kanan Regency by 82.20% while Work Discipline (X2) affects employee performance by 84.30%. Furthermore, Communication (X1) and Work Discipline (X2) together affect the Performance of the Regional Development Planning Agency of Way Kanan Regency employees by 86.90%.